2019
DOI: 10.1016/j.eats.2019.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Open Reduction Internal Fixation of a Traumatic Osteochondral Lesion of the Patella With Bioabsorbable Screw Fixation

Abstract: Osteochondral injuries of the patella occur often in the setting of traumatic patellar dislocations. Early fixation of the displaced fragment(s) is paramount to maintaining the viability of the articular cartilage and the congruency of the patella. Multiple fixation techniques have been described to ensure stable fixation, including wires, screws, and all-suture techniques with both absorbable and nonabsorbable materials. We performed an open reduction and internal fixation of a large traumatic patellar osteoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…After settling, floating materials were filtered onto a 20 μm PCTE membrane filter and visually inspected using a Nikon SMZ745-T microscope. 8 .-This method is a density separation approach that uses both NaCl (ϱ=1.2g/cm 3 ) and sodium iodide (NaI) (ϱ =1.8g/cm 3 ) solutions. Sieved (<1mm) and dried sediment samples (1kg) were initially separated with air induced overflow (AIO), which uses an aerated NaCl solution for density separation.…”
Section: Gilbreath Et Al (2019)mentioning
confidence: 99%
See 1 more Smart Citation
“…After settling, floating materials were filtered onto a 20 μm PCTE membrane filter and visually inspected using a Nikon SMZ745-T microscope. 8 .-This method is a density separation approach that uses both NaCl (ϱ=1.2g/cm 3 ) and sodium iodide (NaI) (ϱ =1.8g/cm 3 ) solutions. Sieved (<1mm) and dried sediment samples (1kg) were initially separated with air induced overflow (AIO), which uses an aerated NaCl solution for density separation.…”
Section: Gilbreath Et Al (2019)mentioning
confidence: 99%
“…With no sediment standard reference material for MPs, methods are developed with an array of sediment and plastic matrices. Sediments may go through pretreatment steps including oven drying [6][7][8] , presieving of coarse or fine materials 7,9 , or chemical oxidation. [9][10][11][12] The method efficacy is often dependent on sediment composition.…”
Section: Introductionmentioning
confidence: 99%
“…The fragment is then reduced to the patella and secured by tying the four suture loops. Nuelle et al 13 describe a similar method for fixation of the osteochondral fragment using bioabsorbable screws. The main difference in this technique and the technique described in this Technical Note is the addition of microfracture in the osteochondral defect.…”
Section: Discussionmentioning
confidence: 99%
“…In 1988, Rae and Khasawneh 17 were the first to successfully use headless cannulated compression screws to fix large osteochondral fragments of the patella. Other authors [7][8][9]18,19 have reported small series of cases and case reports, showing excellent outcomes in acute OCFs managed by ORIF with screw fixation. Gesslein et al, 20 in a series of 36 acute OCFs located on the patellar surface, concluded that fixation shows improved clinical outcomes and is superior as compared with debridement.…”
Section: Discussionmentioning
confidence: 99%